Revision of Noctiliostrebla (Diptera: Streblidae), parasites of bulldog bats (Chiroptera: Noctilionidae: Noctilio) - Alcantara, Daniel Maximo Correa; Graciolli, Gustavo; Nihei, Silvio S. (Zootaxa, 2019)
The Neotropical genus Noctiliostrebla Wenzel (Diptera: Streblidae) is revised after examination of the types of all nominal species, and 11 species are recognized. Seven new species are described, and a lectotype is designated for Lipoptena dubia Rudow. Resulting information on species distributions and host records can be summarized as follows: Noctiliostrebla dubia (Rudow) is restricted to the Amazon region and is a parasite of Noctilio leporinus (Linnaeus) (Chiroptera: Noctilionidae); Noctiliostrebla traubi Wenzel is restricted to Central America and northern South America, being the only species of the genus parasitizing N. leporinus in Central America; the distribution ranges of N. maai Wenzel and N. traubi are similar, but the host of N. maai is N. albiventris Desmarest; Noctiliostrebla aitkeni Wenzel is restricted to northern South America and has only been recorded as parasitizing N. leporinus; Noctiliostrebla ecuadorensis sp. n. occurs only in Ecuador, on N. albiventris; Noctiliostrebla guerreroi sp. n. has only been recorded from the Amazon region on N. albiventris; Noctiliostrebla falsispina sp. n. is restricted to south-central South America and is a parasite of N. leporinus; the distributions of N. lamasi sp. n. and N. falsispina sp. n. are similar, and the two species usually co-occur on N. leporinus; Noctiliostrebla morena sp. n. has a similar distribution to those of N. falsispina sp. n. and N. lamasi sp. n., but parasitizes N. albiventris; Noctiliostrebla pantaneira sp. n. has a similar distribution to N. morena sp. n. and usually co-occurs with it on N. albiventris; Noctiliostrebla caissara sp. n. is restricted to the southeastern coast of South America and is a parasite of N. leporinus. All species are included in a key and illustrated.